The evolution of homogeneity on longitudinal sections during processing by ECAP - Prell, Michaela; Xu, Cheng; Langdon, Terence G. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2008)
An Al-6061 alloy was processed by equal-channel angular pressing at room temperature for one, two, four and six passes and microhardness measurements were recorded along linear traverses on longitudinal planes in the centers of each billet. The results show the average microhardness increases significantly in the first pass although there is a region of lower hardness running in a band near the bottom surface of the billet. Additional but smaller increases in hardness occur in subsequent passes. The hardness values are distributed homogeneously throughout the longitudinal plane after ECAP through six passes although there remains a very narrow region of lower hardness within a distance of ∼0.5 mm adjacent to the bottom surface. When combined with earlier microhardness measurements taken on the Al-6061 alloy on the cross-sectional plane, the results confirm the potential for achieving excellent homogeneity after pressing through a total of six passes. © 2007 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Aluminum alloy; Equal-channel angular pressing; Hardness; Homogeneity; Severe plastic deformation